Transmission and Innovation of Kasidah (Lagu Islam) in Indonesian (1975~) Take a Case Study on Nasida Ria Kasidah Modern in Semarang - Ning-Hui Hung (IJCAS (International Journal of Creative and Arts Studies), 2017)
Indonesian Islamic music has its own performance occasion, musical function, music characteristic, and the style of musical performance. It has lyrics that represent direct relationship between Moslems and God in religion ceremonies. However, the musical structures are changed due to external stimulation coming along with the changes of Indonesian social structure during its development especially in 1975. Kasidah, a sort of Indonesian Islamic music, is the best exemplification to manifest the interaction between social development and music cultural changes, peculiarly performed by the music group of Qasidah Modern Nasida Ria in Semarang, Indonesia. The reason is that kasidah is more liberal than other Islamic music genres in Indonesia, especially on musical performance, usage on instruments, etc. This research sees “music” as a communication system of sound which passes through social usage and cultural contexts in Ethnomusicological perspective. The focus of discussion in on this group to explore some topics in order to comprehend the interaction between social structural development and the innovation of kasidah musical structure in Indonesia, such as the transmission and development of the group Qasidah Modern Nasida Ria, innovation of the group Qasidah Modern Nasida Ria and its music, and the musical function of modern kasidah. By which to understand the current development of kasidah in Indonesia, explore the concept and the role of the word „modern‟ plays in the development of modern kasidah, and point out the cultural syncretism and impact occured in the development of modern kasidah.